The “Jewish Vote” in Canada’s 2025 Federal General Election - Brym, Robert (Canadian Jewish Studies / Études juives canadiennes, 2025)
Contrary to widespread opinion, Jewish voting patterns are not governed solely or sometimes even mainly by the commonly perceived ethno-religious interests of Jews, such as support for Israel and opposition to antisemitism. They are also governed by the same social forces that affect all Canadians. Focusing exclusively on the presumed Jewish interest underlying the Jewish vote prevents us from fully understanding why Jews vote the way they do. This paper seeks to demonstrate as much by examining trends in Jewish voting patterns over time and analyzing the factors that led some Jews to vote Liberal and others to vote Conservative in the 2025 federal general election. Along the way, it also examines the degree to which the Jewish vote helped to elect Jewish candidates. The paper is based mainly on the 2025 Canadian Jewish Voter Study, a web panel survey of five hundred Canadian Jewish adults that was in the field April 15–25, 2025, days before the April 28, 2025, federal general election.